2021
DOI: 10.3390/polym13223939
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Nanostructured Fibrin-Agarose Bone Substitute in a Model of Severely Critical Mandible Bone Defect

Abstract: Critical defects of the mandibular bone are very difficult to manage with currently available materials and technology. In the present work, we generated acellular and cellular substitutes for human bone by tissue engineering using nanostructured fibrin-agarose biomaterials, with and without adipose-tissue-derived mesenchymal stem cells differentiated to the osteogenic lineage using inductive media. Then, these substitutes were evaluated in an immunodeficient animal model of severely critical mandibular bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous studies reported fibrin-agarose as a biological substitute with applications on artificial tissues such as cornea, 23 among others. This study showed that the fibrin-agarose construct formed a three-dimensional structure of such consistency that allowed easy manipulation and consistency that facilitated the incorporation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported fibrin-agarose as a biological substitute with applications on artificial tissues such as cornea, 23 among others. This study showed that the fibrin-agarose construct formed a three-dimensional structure of such consistency that allowed easy manipulation and consistency that facilitated the incorporation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Martin-Piedra et al developed nanostructured fibrin-agarose biomaterials to produce bone substitutes with and without adipose-derived mesenchymal stem cells in immunodeficient animal models, improving the morphofunctional aspects of their maxillofacial structures. 205 A preliminary analysis determined that these cellular substitutes could improve the density of the regenerated tissue and provide isolated islands of bone and cartilage. There are preliminary signs that cellular fibrin-agarose substitutes are useful for the treatment of severely critical mandibular bone defects.…”
Section: Advances In the Design Of Fibrin-based Matrices With Improve...mentioning
confidence: 99%